2012
DOI: 10.1021/ie3012984
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Modeling of Aqueous Ionic Liquid Solutions Using PC-SAFT Equation of State

Abstract: In this work, an equation of state has been utilized for thermodynamic modeling of aqueous ionic liquid (IL) solutions. The proposed equation of state is a combination of perturbed chain statistical associating fluid theory (PC-SAFT) equation of state and mean spherical approximation (MSA) term. In this model, the ion-based approach has been used to adjust the model parameters. The ion parameters have been estimated through simultaneous fitting to experimental mean ionic activity coefficient and liquid density… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 54 publications
(81 reference statements)
0
26
0
Order By: Relevance
“…In this work, the free energy due to the electrostatic interactions between ions is considered by Debye Hückel (DH) theory . In our previous work, the primitive MSA was used for long range interaction. Recent investigations showed that the primitive MSA performs similarly to the DH theory .…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, the free energy due to the electrostatic interactions between ions is considered by Debye Hückel (DH) theory . In our previous work, the primitive MSA was used for long range interaction. Recent investigations showed that the primitive MSA performs similarly to the DH theory .…”
Section: Theorymentioning
confidence: 99%
“…The ion‐specific parameters and ion‐specific coefficients were fitted to experimental activity coefficients and solution densities data up to 473.15 K. Among all available SAFT models, the PC‐SAFT EOS has been widely applied to multitude of the systems including electrolyte solutions. The electrolyte PC‐SAFT versions have been developed by the combination of PC‐SAFT and Debye Hückel (DH) or MSA long range term . Recently, the electrolyte polar PC‐SAFT (ePPC‐SAFT) has been utilized to treat aqueous solution of single salts up to high temperature without requiring temperature‐dependent model parameters .…”
Section: Introductionmentioning
confidence: 99%
“…The optimal values of ν 00 and u 0 /k B for each Table 1. SAFT-HR parameters for pure water in the temperature range of 283-613 K [30] Parameters m ion of a salt are listed in Table 2. Moreover, Table 2 gives the comparison of the results of this work with that of Liu et al [39] who used the NPM MSA model coupled with SAFT EoS [14] for calculating mean ionic activity coefficients of 46 single 1 : 1 electrolytes.…”
Section: Ion Parametersmentioning
confidence: 99%
“…Herzog et al [29] used an NPM term coupled with PC-SAFT EoS to model completely dissociating aqueous alkali halide systems. Shahriari et al [30] used the MSA model coupled PC-SAFT EoS for thermodynamic modeling of aqueous ionic liquid solutions. In this work, to consider the electrostatic interactions between charged particles, the explicit simple version of MSA model [6] is coupled with SAFT-HR EoS [31,32] proposed by Huang and Radosz.…”
Section: Introductionmentioning
confidence: 99%
“…Perturbed-chain statistical fluid theory, PC-SAFT, and hard-sphere, HS, were tested to analysed volumetric and viscometric behaviour, respectively, for [ [9], Shahriari et al [10], Domańska et al [11] and Paduszyníski et al [12].…”
Section: Introductionmentioning
confidence: 99%